Clinically relevant cell culture models and their significance in isolation, pathogenesis, vaccine development, repurposing and screening of new drugs for SARS-CoV-2: a systematic review. (June 2021) - Kumar, Subodh; Sarma, Phulen; Kaur, Hardeep; Prajapat, Manisha; Bhattacharyya, Anusuya; Avti, Pramod; Sehkhar, Nishant; Kaur, Harpinder; Bansal, Seema; Mahendiratta, Saniya; Mahalmani, Vidya M.; Singh, Harvinder; et al.
Highlights: Cell lines are best In-Vitro experimental models for standardization and validation of novel and repurposing of drugs. SARS-CoV-2 entrance is very specific to target cells through ACE2, CD147 and TMPRSS2 receptors. Our systematic review addresses the utility of SARS COV-2 specific cell lines as potential In-Vitro models. Elucidated all In-Vitro studies done for SARS-CoV-2 isolation, pathogenesis, and therapeutics. VeroE6, HEK293, Huh-7 and Caco2 have high ACE2 and TMPRSS2 expression and are potential In-Vitro models for SARS-CoV-2. Abstract: Background: In-Vitro /Cellular evidence is the backbone and vital proof of concept during the development of novel therapeutics as well as drugs repurposing against COVID-19. Choosing an ideal in-vitro model is vital as the virus entry is through ACE2, CD147, and TMPRSS2 dependant and very specific. In this regard, this is the first systematic review addressing the importance of specific cell lines used as potential in-vitro models in the isolation, pathogenesis, and therapeutics for SARS−COV-2. Methods: We searched 17 literature databases with appropriate keywords, and identified 1173 non-duplicate studies. In the present study, 71 articles are included after a careful, thorough screening of the titles and their abstracts for possible inclusion using predefined inclusion/exclusion criteria (PRISMA Guidelines). Results: In the current study, we compiled cell culture-based studies for SARS-CoV-2 and found the best compatible In-Vitro models for SARS-CoV-2 (Vero, VeroE6, HEK293 as well as its variants, Huh-7, Calu-3 2B4, and Caco2). Among other essential cell lines used include LLC-MK2, MDCKII, BHK-21, HepG2, A549, T cell leukemia (MT-2), stems cells based cell line DYR0100for differentiation assays, and embryo-specific NIH3T3 cell line for vaccine production. Conclusion: The Present study provides a detailed summary of all the drugs/compounds screened for drug repurposing and discovery purpose using the in-vitro models for SARS-CoV-2 along with isolation, pathogenesis and vaccine production. This study also suggests that after careful evaluation of all the cell line based studies, Kidney cells (VeroE6, HEK293 along with their clones), liver Huh-7cells, respiratory Calu-3 cells, and intestinal Caco-2 are the most widely used in-vitro models for SARS-CoV-2.